Evaluation of the Effectiveness of CSR Programs on Community Behavior Change in Forest Conservation - Wiwin Suhartanto; Erny Tajib (Pelopor Publikasi Akademika, 2023)
Global warming can cause climate change and have a broad impact on people's lives. The increase in global temperature is caused by increased carbon emissions due to deforestation in various countries. Forests play a very important role in solving the carbon emissions problem. One source of carbon dioxide emissions throughout the world is the existence of Tropical Forests. One of the countries that has the largest tropical forest in the world is Indonesia. Kalimantan Island is one of the largest islands and has the largest forest area in Indonesia. This research was conducted at PT. Asmin Bara Bronang who runs the company's CSR program. The variables are the implementation of CSR programs, the targets of the CSR programs implemented and their impact on changes in community behavior in forest conservation. This research also discusses the relationship between implementing CSR programs with ISO 26000 and the Sustainable Development Goals. The sampling technique used was purposive sampling. Data collection was carried out through interviews with 43 sources consisting of PT Asmin Bara Bronang employees and community recipients of the CSR program. The collected data was then analyzed using the content analysis method. Research shows PT. Asmin Bara Bronang carries out a CSR program contributes to changes in the behavior of the Dayak Ngaju community in efforts to preserve Kalimantan's forests. It is hoped that this research can complement the literature regarding the implementation of CSR programs in supporting forest conservation programs